intralingual open subtitling in Flanders: audiovisual translation, linguistic variation and audience needs - Aline Remael; Reinhild Vandekerckhove; Annick De Houwer (JoSTrans: The Journal of Specialised Translation)
This article presents an overview of the main findings of an interdisciplinary research project carried out by scholars from a department of translation and interpreting, a department of communication science and a department of linguistics. The project investigated Dutch open subtitling1 of native speakers of either northern Dutch or a Flemish (regional) variant of Dutch on Flemish television. Its corpus consisted of 793 programmes or 380 hours of broadcasting time.